Increased Ratio of CD14++CD80+ Cells/CD14++CD163+ Cells in the Infrapatellar Fat Pad of End-Stage Arthropathy Patients - Ma, Shuhe; Murakami, Kosaku; Saito, Rintaro; Ito, Hiromu; Murata, Koichi; Nishitani, Kohei; Hashimoto, Motomu; Tanaka, Masao; Taniguchi, Masahi; Kitagori, Koji; Akizuki, Shuji; Nakashima, Ran; et al. (Frontiers in Immunology, 2021)
Abstract Objectives. This study sought to identify the ratio of M1/M2 cells in the infrapatellar fat pads (IFP) and subcutaneous fat tissues (SC) of osteoarthritis (OA) and rheumatoid arthritis (RA) patients. The clinical features of OA and RA patients treated with or without biological disease-modifying anti-rheumatic drugs (bDMARDs) were also assessed. Methods. IFP and SC were collected from patients with OA and RA undergoing total knee arthroplasty (TKA). CD14 positive cells were then isolated from these samples. Flow cytometry was used to determine the number of CD14++CD80+ cells and CD14++CD163+ cells. The expression levels of lipid transcription factors, such as sterol regulatory element-binding protein 1 (SREBP1) and liver X receptor alpha (LXRA), and inflammatory cytokines were also evaluated. Results. Twenty OA patients and 22 RA patients were enrolled in this study. Ten of the RA patients (45.4%) received bDAMRDs before TKA. On average, a 5-fold increase in the number of CD14 positive cells and lower expression levels of SREBP1C and LXRA were observed in OA IFP relative to OA SC; however, these results were not obtained from the RA samples. The median ratio of CD14++CD80+ cells/CD14++CD163+ cells of OA IFP was 0.87 (0.76-1.09, interquartile range), which is higher to that of OA SC with a lower ratio (p= 0.05835). Conclusions. The quantity and quality of CD14 positive cells differed between IFP and SC in arthropathy patients. To our knowledge, this is the first study to characterize the ratio of M1/M2 cells in the IFP and SC of end-stage OA and RA patients. The increased ratio of CD14++CD80+ cells/CD14++CD163+ cells in the IFP from patients with OA and RA treated with bDMARDs indicated inflammation localized in the IFP. As adipose tissue-derived innate immune cells were revealed as one of the targets for regulating inflammation, further analysis of these cells in the IFP may reveal new therapeutic strategies for inflammatory joint diseases.